Coordination Compounds of Co(II), Ni(II) and Cu(II) with Thiosemicarbazone of a Series of Quinazolone Derivatives: Their Preparation, Characterization and Structural Investigation - Rai, B.K.; Baluni, Akhilesh (Asian Journal of Chemistry, 2010)
Complexes of Co(II), Ni(II) , and Cu(II) with 2-phenyl-[-3- (hydroxyethyl)]-3,1-( 4H)-quinazoline-4-thiosemicarbazone (PHEQTSC), 2-phenyl-6,8-dibromo-[3-(hydroxy-ethyl)]-3,1-( 4H)-quinazoline-4-thiosemicarbazone (PDBHEQTSC) and 2-phenyl-6-bromo-[3-(hydroxyethyl)]-3,1- (4H)-quinazoline-4-thiosemicarbazone (PBHEQTSC) have been synthesized and characterised on the basis of elemental analysis, IR, electronic spectra, conductivity and magnetic moment data. The ligand can function as a binegative tridentate chelating agent coordinating through nitrogen, oxygen and sulphur atoms with the metal ions forming complexes in molar ratio 2: 1 having the empirical formula [ML1-32] and can be presumed to have octahedral geometry.